Pengaruh Model Kooperatif Tipe Word Square Berbantu LearningApps Terhadap Keaktifan Peserta Didik pada Pembelajaran Pendidikan Pancasila: Penelitian - Mepina Nursyabani; Susan Fitriasari; Nisrina Nurul Insani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effect of the word square cooperative learning model assisted by LearningApps on student activeness in Pancasila Education learning. This study was conducted at SMP Negeri 1 Rajapolah. The research approach used was quantitative with a quasi-experimental method and a non-equivalent control group design. The research subjects were 60 students from two classes VIII. The instrument used was a case study essay test and was analyzed using SPSS. The results showed that the level of student learning activeness in the experimental class increased significantly compared to the control class. The experimental class reached the very high category, while the control class was in the low category. These findings indicate that the word square cooperative learning model assisted by LearningApps has an effect on increasing student activeness.